The cell-intrinsic circadian clock is dispensable for lateral posterior clock neuron regulation of Drosophila rest-activity rhythms - Charlene Y.P. Guerrero; Madelyn R. Cusick; Amanda J. Samaras; Natalie S. Shamon; Daniel J. Cavanaugh (Neurobiology of Sleep and Circadian Rhythms)
Circadian control of behavior arises from intercommunication among a distributed network of circadian clock neurons in the brain. Single-cell sequencing and brain connectome data support the division of the ∼240 brain clock neurons in Drosophila into ∼20 subclusters, and functional studies demonstrate that these populations differentially contribute to behavioral outputs. Here, we have used genetic tools that enable highly selective, cell-specific manipulations to investigate the role of molecular clock function and neuronal activity within the lateral posterior clock neurons (LPNs) in the regulation of rest-activity rhythms. We find that genetic silencing of these neurons, which compromises signaling with downstream neuronal targets, substantially reduces the strength of free-running rest-activity rhythms. In contrast, locomotor activity patterns are robust to CRISPR-mediated disruption of molecular clock cycling within the LPNs. We conclude that the LPNs act as driven oscillators that retain the capacity to transmit circadian information in the absence of cell-intrinsic molecular clocks.